Key writers on art the twentieth century - Murray, Chris (London Routledge, 2003)
The Twentieth Century offers a unique and authoritative guide to modern responses to art. Featuring 48 essays on the most important twentieth century writers and thinkers and written by an international panel of expert contributors, it introduces readers to key approaches and analytical tools used in the study of contemporary art. It discusses writers such as Adorno, Barthes, Benjamin, Freud, Greenberg, Heuser, Kristeva, Merleau-Ponty, Pollock, Read and Sontag.
Keywords: Art criticism